Growth and quality of chives in hydroponic system with concentrations of magnesium sulfate - Paulus,Dalva (2022)
ABSTRACT Chives are popular herbs, and highly appreciated by consumers. The experiment was conducted in the period from September to November 2020 in a greenhouse, located at the Federal University of Technology, Paraná, Brazil. This study aimed to evaluate the growth, physiological responses, and quality attributes of chives grown in hydroponic systems containing different concentrations of magnesium sulfate. The experimental design was randomized blocks, and the treatments consisted of a standard solution with the addition of magnesium sulfate at the following doses (g/L): standard solution 0.4; 0.42, 0.44; 0.46, and 0.48, with four repetitions per treatment. The analyzed variables were physiological indicators and growth; physical-chemical characteristics and nutrient content in tissues. The dose of 0.48 g/L resulted in the highest number of leaves (47.3) and contributed to 44% reduction in leaf drop, thereby positively influencing growth with higher fresh mass (231.40 g/plant). The relative chlorophyll index (58.64) obtained at 0.48 g/L dose revealed an increase in the chlorophyll content and, consequently, in the green color of the plants, with °hue angle of 140.54. Greener leaves is a visual aspect preferred by consumers. In addition, the higher concentration of magnesium sulfate provided 50.7% increase in the content of soluble solids and 50.6% rise in phenolic compounds. The dose of 0.48 g/L magnesium sulfate contributed to reduced leaf fall, improved visual appearance, greater bioactive compounds, and enhanced leaf sweetness to meet the quality standards that consumers expect for this condiment.